Heterogenity of childhood absence epilepsies - F. I. Gusyakov; M. V. Belousov; E. A. Morozova; D. G. Gazizova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Summary. In connection with the growing volume of scientific data on the genetic problems of generalized epilepsy in recent decades, the ambiguity of the therapeutic tactics and prognosis of this cohort of patients has become obvious based solely on the phenotypic characteristics of the patient. It is known that epilepsies with similar phenotypes show a different genetic nature, different pathogenesis of the development of epileptogenesis and response to therapy. The outcomes also differ, both in terms of seizure control and in terms of cognitive functions.The article presents an overview of the factors that must be taken into account when manifesting childhood absentee epilepsy: the child’s gender, types of seizures, cognitive profile, results of electroencephalography and neuroimaging. Attention is paid to the genes that determine the development of these forms of epilepsy in children.